SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON PESERTA OLIMPIADE SAINS NASIONAL (OSN) MENGGUNAKAN METODE ELIMINATION AND CHOICE TRANSLATION REALITY (ELECTRE) (STUDI KASUS : SD NEGERI NO 050590 PADANG CERMIN) - Arinal Husnah; Budi Serasi Ginting; Marto Sihombing (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
SD Negeri 050590 Padang Cermin is one of the elementary schools that sends students every year to attend the National Science Olympiad (OSN) at the sub-district level. The selection of students who take part in the Olympics is usually carried out by the teacher / principal manually through writing and considering the academic grades of students, so it takes a long time because they select students one by one first. A decision support system is a software product developed specifically to assist in the decision-making process. By involving a method, a system will produce an appropriate decision for data selection. The Elimination And Choice Translation Reality (ELECTRE) method is a multi-criteria decision-making method based on the Outranking concept by using paired comparisons of alternatives based on each appropriate criterion. The ELECTRE method is used in conditions where alternatives that do not meet the criteria are eliminated, and suitable alternatives can be generated. This system uses the PHP programming language and the database uses MySQL. There are six criteria, report card value, math score, science score, skills, behavior, and attendance. Based on the results of the calculation of the ELECTRE method from 5 samples of students, the results obtained by the name of the student Dinda Malika Ayu are the students with the highest score analysis results.